Arylation of quinoxalinones at room temperature under metal and base free-conditions - Badhani, Gaurav; Adimurthy, Subbarayappa (Monatshefte für Chemie, 2024)
A mild and efficient method for the arylation of quinoxalinones are described using aryldiazonium tetrafluoroborates as aryl source. Reactions proceeds at room temperature in a short reaction time of 1 h without metal catalysts and bases. Broad functional group tolerance was observed with good yields of products even at gram scale reaction. Control experiments suggest that the reactions proceed through a radical pathway. Furthermore, the present protocol applied for the successive synthesis of three biologically active molecules. Overall, the method offers a convenient and versatile approach for the synthesis of arylated quinoxalinones. Graphical abstract